2012
DOI: 10.3109/01612840.2011.624258
|View full text |Cite
|
Sign up to set email alerts
|

Pains, Joys, and Secrets: Nurse-Led Group Therapy for Older Adults with Depression

Abstract: This is the first study of nurse-led group therapy in Mexico. Forty-one depressed older adults with a median age of 71 participated in nurse-led cognitive behavioral group therapy once a week for 12 weeks. Participants' scores on the Patient Health Questionaire-9 showed mild to moderate improvement. Participants experienced positive results in personal growth, changing negative thoughts, and relationships with family. An important therapeutic factor was the support of fellow group members. The nurses experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Cappeliez (2000) tracked the intensity of depression during weekly group CBT, finding a gradual decrease in depressive symptoms. Nance (2012) found mild to moderate improvement for depression and overall improvements in personal growth, changing negative thoughts and relationships with family members.…”
mentioning
confidence: 99%
“…Cappeliez (2000) tracked the intensity of depression during weekly group CBT, finding a gradual decrease in depressive symptoms. Nance (2012) found mild to moderate improvement for depression and overall improvements in personal growth, changing negative thoughts and relationships with family members.…”
mentioning
confidence: 99%
“…Further, a 25-year follow-up of nurses administering CBT found a considerable contribution to mental health service provision, specifically in primary care settings [8]. Other studies have also demonstrated the efficacy of nurse-led CBT for a wide range of mental disorders [[9], [10], [11], [12], [13], [14]]. According to a document from Horatio (European Psychiatric Nurses), currently in the UK 90% of all CBT therapists have a psychiatric nursing background [15].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults’ positive therapy engagement experiences have been found to be associated with the perceived benefits provided by psychological therapies that have specific working mechanisms (Camacho et al., 2018; Choi et al., 2013; Dakin & Areán, 2013; Nance, 2012; Simmonds et al., 2013; Williams et al., 2018). Older adults thought that self‐help groups were beneficial because the groups provided opportunities to interact with other older adults with depression (Stark et al., 2018).…”
Section: Resultsmentioning
confidence: 99%